THE INFLUENCE OF BRAND IMAGE, ATMOSPHERE STORE AND PRICE PERCEPTION ON CUSTOMER SATISFACTION OF STARBUCKS GRAND PAKUWON - FOOD JUNCTION THROUGH PURCHASING DECISIONS - Utari, Woro; Permadi, Galih (Jurnal Riset Manajemen Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha Program Magister Manajemen, 2024)
The objective of this study is to examine the impact of brand image, atmosphere, and price perception on customer satisfaction in relation to purchasing decisions. The research design employed is explanatory research through a quantitative approach. All customers who visited Starbucks Grand Pakuwon-Food Junction in 2023 were considered as the study population. Technical terms will be explained in full at the first use. A total of 100 respondents were selected through quota sampling method. The data collected was analysed using path analysis and validity and reliability testing. The study findings indicate that the variables of Brand Image, Atmosphere, and Decisions were categorized as good, while Price and Satisfaction variables were classified as good enough. Specifically, Brand image, atmosphere, and price positively and significantly influence purchasing decisions. Directly, brand image, atmosphere, price, and purchase decisions significantly and positively impact customer satisfaction. Indirectly, purchasing decisions can intervene a significant positive impact on brand image, atmosphere, price, and decisions on customer satisfaction.